Globalization of Central Asia - Mubeen Adnan; Bushra Fatima (Journal of Political Studies, 2015)
Central Asia which can be termed as Five Stans Asiaor Multi State Asia, internationally a dominant region from both Eastern and Western perspectives, having two major powers involvement that is Russia and China, along with the regional powers named as Kazakhstan, Kyrgyzstan, Turkmenistan, Uzbekistan and Tajikistan so called five pillars of Central Asia. Central Asia is a region with socio-economic, political, cultural, geographical and geostrategic importance. The main aim of writing this article is the economic role of Central Asia in the globalization process, also Central Asia’s role in the world politics in which how Russians extremely authoritatively rule this state and how China as a sound actor involved its performance to attain its national interest. However, the United States of America (USA), Afghanistan, Pakistan, European Union(EU),Germany, Turkey, Iran and many other countries of the world show their center of interest from the beneficial point of view for their own state’s purpose. Globalization is basically a phenomenon of increasing integration of social, cultural, political, economic, transport, telecommunication in the international system. Central Asia’s historical view till present modern scenarios is highlighted. Central Asia and globalization is mainly concerned with the macro- level relationships, it has certain issues as well like that of identity, population, and language, decisions as well as policies that play as an engine in terms of the world-clock matters